The Influence of Principals' Managerial Competence, Academic Supervision and Teachers' Education Level on The Performance of Public Junior High School Teachers in Kuala Kampar Sub-District - Hamdan Hamdan; Lia Yuliana; Khaled Youssouf (Journal of Loomingulisus ja Innovatsioon, 2026)
The success of education is highly dependent on the interconnectedness of supporting factors that contribute to improving the quality of education. One of the main factors is optimal teacher performance in achieving student learning outcomes. This study aims to analyze the effect of the principal's managerial competence, academic supervision, and education level on the performance of public junior high school teachers in Kuala Kampar District. This study used a descriptive quantitative approach with a population of all public junior high school teachers in Kuala Kampar District, Riau Province, totaling 78 people. The saturated sample method was applied, so that the entire population was used as a research sample. Data collection was done through a questionnaire (survey), and data analysis using descriptive analysis techniques and multiple linear regression. The results showed that: (1) principals' managerial competence has a positive and significant effect on teacher performance, (2) academic supervision has a positive and significant effect on teacher performance, (3) teachers' education level has a positive and significant effect on teacher performance, and (4) simultaneously, the three independent variables have a positive and significant effect on teacher performance with the regression equation Y = 2.672 + 0.832X? + 0.618X? + 0.713X?. The constant value of 2.672 indicates that if all independent variables are zero, then teacher performance is still worth 2.672. The regression coefficients indicate that each one-unit increase in principals' managerial competence, academic supervision, and education level will increase teacher performance by 0.832; 0.618; and 0.713 respectively, assuming other variables remain constant. This finding confirms that efforts to improve teacher performance need to consider improving principals' managerial competence, the effectiveness of academic supervision, and improving teachers' education levels. Thus, the results of this study can serve as a reference for stakeholders in designing more effective policies to improve the quality of education.